2020
DOI: 10.1056/nejmc2004973
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol and Surface Stability of SARS-CoV-2 as Compared with SARS-CoV-1

Abstract: To the Editor: A novel human coronavirus that is now named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (formerly called emerged in Wuhan, China, in late 2019 and is now causing a pandemic. 1 We analyzed the aerosol and surface stability of SARS-CoV-2 and compared it with SARS-CoV-1, the most closely related human coronavirus. 2 We evaluated the stability of SARS-CoV-2 and SARS-CoV-1 in aerosols and on various surfaces and estimated their decay rates using a Bayesian regression model (see t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

156
8,298
13
529

Year Published

2020
2020
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 8,576 publications
(9,340 citation statements)
references
References 4 publications
156
8,298
13
529
Order By: Relevance
“…SARS-CoV2 is transmitted primarily after viral particles are inhaled and enter the respiratory tract (1). In addition, the virus can survive for 24-72 hours on surfaces, depending on the type of surface, which enables fomite transmission (14).…”
Section: Pathogenesis and Transmissionmentioning
confidence: 99%
“…SARS-CoV2 is transmitted primarily after viral particles are inhaled and enter the respiratory tract (1). In addition, the virus can survive for 24-72 hours on surfaces, depending on the type of surface, which enables fomite transmission (14).…”
Section: Pathogenesis and Transmissionmentioning
confidence: 99%
“…Although it was found that the use of crowded public transport vehicles can be associated with the acquisition of infectious diseases, it can be argued that these findings do not support the effectiveness of suspending mass urban transport systems as a pandemic countermeasure aimed at reducing or slowing population spread because, whatever the relevance of public transport is to individuallevel risk, household exposure most likely poses a greater threat (Williams et al, 2010;Cooley et al, 2011).…”
Section: Public Transportmentioning
confidence: 99%
“…Exposure to the Huanan seafood market was common among the earliest cases contributing to the SARS-CoV2 epidemic in China suggesting that this was a zoonotic disease with an intermediate animal host (non-aquatic animals were sold in the market) (35) (38). In fact, the Japanese National Institute of Infectious Disease reported detection of SARS-CoV2 RNA on surfaces in the cabins of symptomatic and asymptomatic passengers on the Diamond Princess up to 17 days after they were vacated (39).…”
Section: Transmissionmentioning
confidence: 99%